Factors Related to Stunting in Toddlers Aged 6-24 Months (Medico Legal Update, 2020)
Stunting is one of worrying nutritional problems in Indonesia as its prevalence grows every year. The generalobjective of this study is to determine factors related to stunting. This study used cross-sectional approachconducted in Kendari City and Semarang City from April to December 2019. The population was childrenunder two years old in Kendari City and Semarang City. Data were analyzed quantitatively, consisting ofunivariate and bivariate analysis with the help of SPSS. Data analyzed were presented in the form of tableand description to discuss the results. The results showed that variables that were significantly correlatedwith stunting in this study were birth weight (p = 0.014), feeding (p = 0.014), mother’s height (p = 0.004),ANC (p = 0.008), mother’s education (p = 0.007), drinking water use (p = 0.0001), toilet use (0.047). Toprevent stunting, it is suggested based on this study to focus on variables like feeding suitability, mother’sweight, ANC examination, drinking water use and toilet use.